Representing grounding line migration in synchronous coupling between a marine ice sheet model and a z -coordinate ocean model - Goldberg, D.N.; Snow, Kate; Holland, Paul; Jordan, Jim; Campin, Jean-Michel; Heimbach, Patrick; Arthern, Robert; Jenkins, Adrian (Ocean Modelling, 2018)
Synchronous coupling is developed between an ice sheet model and a z-coordinate ocean model (the MITgcm). A previously-developed scheme to allow continuous vertical movement of the ice-ocean interface of a floating ice shelf (“vertical coupling”) is built upon to allow continuous movement of the grounding line, or point of floatation of the ice sheet (“horizontal coupling”). Horizontal coupling is implemented through the maintenance of a thin layer of ocean ( ∼ 1 m) under grounded ice, which is inflated into the real ocean as the ice ungrounds. This is accomplished through a modification of the ocean model’s nonlinear free surface evolution in a manner akin to a hydrological model in the presence of steep bathymetry. The coupled model is applied to a number of idealized geometries and shown to successfully represent ocean-forced marine ice sheet retreat while maintaining a continuous ocean circulation.